2015
DOI: 10.1038/hr.2014.170
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict the presence of coronary lesions from blood pressure measurement? A new clinical method

Abstract: The roles of arterial function and structure in cardiovascular physiology have expanded with the development of a variety of parameters that evaluate arterial stiffness. Markers of arterial stiffness have been correlated with cardiovascular outcomes. We aimed to find a simple, clinical, noninvasive method to predict atherosclerosis that leads to the development of coronary artery disease (CAD). We aimed to find a simple, clinical, noninvasive method to predict atherosclerosis that leads to the development of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This is consistent with the fi nding of our previous study which shows the presence of a highly positive correlation between Tahlawi gap and hypertension [7].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is consistent with the fi nding of our previous study which shows the presence of a highly positive correlation between Tahlawi gap and hypertension [7].…”
Section: Discussionsupporting
confidence: 82%
“…These oscillations are refl ected to the mercury in the sphygmomanometer earlier than the sound that is auscultated. This difference generates the Tahlawi gap [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also using a mathematical model, Liu et al [7] demonstrated that calculating SBP and DBP from the oscillometric envelope with fixed ratios measurement produces errors that increase when the arterial wall stiffens and/or the PP increases. Differences between oscillometric and auscultatory BP measurements are indeed greater in study participants with increased arterial wall stiffness [16], and have been proposed as an indicator of arterial stiffness, predictive of coronary lesions [33]. It is therefore all the more interesting that our technique yielded its best correlation with Korotkoff sounds in older study participants and in study participants with cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 93%